Identification of genetic variants or genes that are associated with Homoharringtonine (HHT) response through a genome-wide association study in human lymphoblastoid cell lines (LCLs) - Tong, Yin; Niu, Nifang; Jenkins, Gregory; Batzler, Anthony; Li, Liang; Kalari, Krishna R.; Wang, Liewei (Frontiers in Genetics, 2015)
Homoharringtonine (HHT) has been widely used in China to treat patients with acute and chronic myeloid leukemia for decades. Since response to HHT varies among patients, our study aimed to identify biomarkers that might influence the response to HHT using a panel of various human lymphoblastoid cell lines (LCLs). Genome-wide association (GWA) analysis using single nucleotide polymorphism (SNP) and mRNA expression data was assessed for association with cytotoxicity to HHT in LCLs. Integrated analysis among SNPS, expression, AUC value was also performed to help select candidate genes for further functional characterization. Functional validation of candidate genes was performed using leukemia cell lines (U937, K562). Candidate genes were knocked down using specific siRNA and its response to HHT was assessed using MTS assay. We found that 15 expression probes were associated with HHT AUC with P value<10-4, and 96 individual probe sets with P value<10-3. Eighteen SNPs were associated with HHT AUC with P<10-5 and 281 SNPs with P<10-4. The integrated analysis identified 4 unique SNPs that were associated with both expression and AUC. Functional validation using siRNA knockdown in leukemia cell lines showed that knocking down CCDC88A, CTBP2, SOCS4 genes in U937 and K562 cells significantly altered HHT cytotoxicity. In summary, this study performed with LCLs can help to identify novel biomarker that might contribute to variation in response to HHT therapy.